SOCIAL MEDIA AS A TOOL FOR LANGUAGE LEARNING: FOSTERING LEARNER AUTONOMY AND DIGITAL LITERACY - Odilova Fotimakhon (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the transformative role of social media platforms as comprehensive tools for autonomous language learning. In the contemporary educational landscape, the shift from traditional, teacher-led instruction to learner- centered agency is facilitated by digital environments. By analyzing the pedagogical potential of platforms like Instagram, YouTube, and Telegram, the study highlights how "incidental learning" and "digital literacy" contribute to long-term linguistic retention and communicative competence. The research argues that social media provides a "customized curriculum" that enhances intrinsic motivation and prepares EFL learners for the complexities of global, real-world communication.